Modulation of daily PM2.5 concentrations over China in winter by large-scale circulation and climate change - Z. Jia; C. Ordóñez; R. M. Doherty; O. Wild; S. T. Turnock; S. T. Turnock; F. M. O'Connor (Atmospheric Chemistry and Physics, 2023)
We use the United Kingdom Earth System Model, UKESM1, to investigate the influence of the winter large-scale circulation on daily concentrations of PM2.5 (particulate matter with an aerodynamic diameter of 2.5 µm or less) and their sensitivity to emissions over major populated regions of China over the period 1999–2019. We focus on the Yangtze River delta (YRD), where weak flow of cold, dry air from the north and weak inflow of maritime air are particularly conducive to air pollution. These provide favourable conditions for the accumulation of local pollution but limit the transport of air pollutants into the region from the north. Based on the dominant large-scale circulation, we construct a new index using the north–south pressure gradient and apply it to characterise PM2.5 concentrations over the region. We show that this index can effectively distinguish different levels of pollution over YRD and explain changes in PM2.5 sensitivity to emissions from local and surrounding regions. We then project future changes in PM2.5 concentrations using this index and find an increase in PM2.5 concentrations over the region due to climate change that is likely to partially offset the effect of emission control measures in the near-term future. To benefit from future emission reductions, more stringent emission controls are required to offset the effects of climate change.